An fMRI study of finger tapping in children and adults. Issue 8 (2nd April 2018) - Turesky, Ted K.; Olulade, Olumide A.; Luetje, Megan M.; Eden, Guinevere F.
Abstract: Functional brain imaging studies have characterized the neural bases of voluntary movement for finger tapping in adults, but equivalent information for children is lacking. When contrasted to adults, one would expect children to have relatively greater activation, reflecting compensation for an underdeveloped motor system combined with less experience in the execution of voluntary movement. To test this hypothesis, we acquired functional magnetic resonance imaging (fMRI) data on 17 healthy right‐handed children (7.48 ± 0.66 years) and 15 adults (24.9 ± 2.9 years) while they performed an irregularly paced finger‐tapping task in response to a visual cue (left‐ and right‐hand examined separately). Whole‐brain within‐group analyses revealed that finger tapping in either age group and for either hand activated contralateral SM1, SMA, ipsilateral anterior cerebellum, and occipital cortices. We used an ANOVA factorial design to test for main effects of Age Group (children vs adults), Hand (left vs. right), and their interactions. For main effects of Age Group, children showed relatively greater activity in left SM1 (extending into bilateral SMA), and, surprisingly, adults exhibited relatively greater activity in right pre‐SMA/SMA (extending into left pre‐SMA/SMA), right lateral globus pallidus, left putamen, and right anterior cerebellum. The interaction of Age Group × Hand revealed that while both groups activated right SM1 during left finger tapping and exhibited signal decreases (i.e., below fixation baseline) during right finger tapping, both these responses were attenuated in children relative to adults. These data provide an important foundation by which to study children with motor disorders.